2011
DOI: 10.1007/s00595-011-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 and interleukin 8 play important roles in systemic inflammatory response syndrome of meconium peritonitis

Abstract: Interleukin 6 and interleukin 8 play important roles in the inflammatory response syndrome associated with meconium peritonitis, and drainage of cystic fluid did not completely suppress this inflammation. To lessen the high morbidity of meconium peritonitis, efforts should be made to suppress the inflammatory response using new treatment strategies, such as administration of steroids or anti-cytokine therapy to supplement cystic drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Therefore, we hypothesized that maternal anti‐fetal rejection is linked to a stereotypical derangement of the systemic fetal chemokine milieu, specifically T cell chemokines, just as intra‐amniotic infection/inflammation (IAI) is associated with an elevation of the fetal plasma concentration of IL‐6 . The latter condition observed in human fetuses of patients with preterm labor and preterm pre‐labor rupture of membranes (PPROM) was termed the ‘fetal inflammatory response syndrome’ (FIRS) and has been associated with a higher rate of adverse neonatal outcome, a short interval to delivery, and multi‐systemic involvement . We have recently reported that an elevation of amniotic fluid CXCL10 concentration during the mid‐trimester is a risk factor for preterm delivery after 32 weeks of gestation, while an elevation of amniotic fluid IL‐6 concentration is associated with preterm delivery before 32 weeks of gestation .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that maternal anti‐fetal rejection is linked to a stereotypical derangement of the systemic fetal chemokine milieu, specifically T cell chemokines, just as intra‐amniotic infection/inflammation (IAI) is associated with an elevation of the fetal plasma concentration of IL‐6 . The latter condition observed in human fetuses of patients with preterm labor and preterm pre‐labor rupture of membranes (PPROM) was termed the ‘fetal inflammatory response syndrome’ (FIRS) and has been associated with a higher rate of adverse neonatal outcome, a short interval to delivery, and multi‐systemic involvement . We have recently reported that an elevation of amniotic fluid CXCL10 concentration during the mid‐trimester is a risk factor for preterm delivery after 32 weeks of gestation, while an elevation of amniotic fluid IL‐6 concentration is associated with preterm delivery before 32 weeks of gestation .…”
Section: Introductionmentioning
confidence: 99%
“…Perforation is associated with bowel obstruction and/or ischemia, which can be caused by intestinal atresia, volvulus, viral infection, ischemia in the mesentery, or cystic fibrosis . Meconium promotes intraperitoneal inflammatory reactions by activating macrophages and inflammatory mediators . The inflammatory reaction can cause intraperitoneal adhesions and damage to the intestinal wall and circulation.…”
Section: Introductionmentioning
confidence: 72%
“…2 Meconium promotes intraperitoneal inflammatory reactions by activating macrophages and inflammatory mediators. 3,4 The inflammatory reaction can cause intraperitoneal adhesions and damage to the intestinal wall and circulation. Some of the perforations may seal spontaneously during pregnancy.…”
mentioning
confidence: 99%
“…Reported causes of neonatal death include prematurity, necrotizing enterocolitis, and postoperative sepsis. [25] Furthermore, the SIRS has been reported as a possible complication,[3] but there are no previous reports of this complication during the fetal period.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Meanwhile, some affected infants result in death, and systemic inflammatory response syndrome (SIRS) is thought to be a possible cause in the field of neonatology. [3]…”
Section: Introductionmentioning
confidence: 99%